(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. Dall’ “aggiornamento” alla “società aperta” - 3. Prospettive di una riflessione - 4. Il superamento della “dicotomia bioetica” nell’era di Papa Francesco - 5. Conclusione. From the "submerged schism" to the era of Pope Francis ABSTRACT: “The submerged schism” by Pietro Prini appears as a new research perspective that seems to overwhelm the distinction between “Catholic bioethics and lay bioethics” and, so, the existence of “two ethical models or paradigms”. From the “upgrading”, through the “open society”, it is achieved to the “overcoming” of the “closed society” and to “the era of Pope Francis” on which the reflection does not seem to be focused yet.